Idiopathic CD4 lymphocytopenia presenting as refractory cryptococcal meningitis - Sharma, A. (Medknow Publications, 2010)
Idiopathic CD4 T-lymphocytopenia (ICL) is a syndrome characterized by depletion of CD4 T-cells without evidence of human immunodeficiency virus (HIV) infection. There are a few reported cases of ICL associated with different diseases and clinical conditions, most commonly the opportunistic infections like Tuberculosis, fungal and parasitic diseases which are also seen in HIV-positive patients. We report a case without risk factors or laboratory evidence of HIV infection who presented with refractory cryptococcal meningitis and was found to have ICL.